STRATEGI GURU DI SDN JELEGONG 01 DALAM MENGEMBANGKAN MINAT DAN BAKAT SISWA YANG BELUM DIADAKANNYA KEGIATAN EKSTRAKURIKULER - Bunga Bhagasasih Al-Kansa; Yayang Furi Furnamasari (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
Elementary schools for children aged 4 to 6 years usually have extracurricular activities at all levels of education, from junior high and high schools to academic schools and universities. The extracurricular activity policy is part of the policy of the Ministry of National Education, which before the reform was called the Ministry of Education and Culture. To support the implementation of the extracurricular program at SDN Jelegong 01 it is necessary to have various instructions and guidelines, both regarding the material and activities, with the hope that the extracurricular program can be carried out in accordance with the objectives outlined. This research approach is a qualitative descriptive case study type approach, where this research focuses more on the results of data collection from certain informants or respondents; the data needed is the distribution of teacher data that does not need to be quantified, and describes what objective conditions are in accordance with the teacher's effective strategy in developing students' interests and skills at SDN Jelegong 01 through informative presentations. The techniques used are interviews, observation and documentation. With this research, the researcher intends to understand, study and develop strategies and evaluations in developing the interests and talents of students at SDN Jelegong 01 Rancaekek.